GingerRoot: A Novel DNA Transposon Encoding Integrase-Related Transposase in Plants and Animals - Cerbin, Stefan (Genome Biol Evol, 2019)
Transposable elements represent the largest components of many eukaryotic genomes and different genomes harbor different combinations of elements. Here, we discovered a novel DNA transposon in the genome of the clubmoss Selaginella lepidophylla. Further searching for related sequences to the conserved DDE region uncovered the presence of this superfamily of elements in fish, coral, sea anemone, and other animal species. However, this element appears restricted to Bryophytes and Lycophytes in plants. This transposon, named GingerRoot, is associated with a 6 bp (base pair) target site duplication, and 100–150 bp terminal inverted repeats. Analysis of transposase sequences identified the DDE motif, a catalytic domain, which shows similarity to the integrase of Gypsy-like long terminal repeat retrotransposons, the most abundant component in plant genomes. A total of 77 intact and several hundred truncated copies of GingerRoot elements were identified in S. lepidophylla. Like Gypsy retrotransposons, GingerRoots show a lack of insertion preference near genes, which contrasts to the compact genome size of about 100 Mb. Nevertheless, a considerable portion of GingerRoot elements was found to carry gene fragments, suggesting the capacity of duplicating gene sequences is unlikely attributed to the proximity to genes. Elements carrying gene fragments appear to be less methylated, more diverged, and more distal to genes than those without gene fragments, indicating they are preferentially retained in gene-poor regions. This study has identified a broadly dispersed, novel DNA transposon, and the first plant DNA transposon with an integrase-related transposase, suggesting the possibility of de novo formation of Gypsy-like elements in plants.